PERAN IBU DALAM MENANAMKAN KEMANDIRIAN ANAK USIA DINI DI LINGKUNGAN KELUARGA (STUDI KASUS PADA IBU YANG BEKERJA SEBAGAI PEMBANTU RUMAH TANGGA) - Syelfiyana, Indriyan; Ali, Musyafa; Fauzi, Fauzi (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2022)
Family as the first educational institution for children has an important role in instilling child independence. Through activities to educate, guide, and provide care to children, the cultivation of independence can be done in the family. The study aims to find out, discover, and explain the role of working mothers as domestic helpers in instilling early childhood independence in the family environment. This research is field research or field research using qualitative descriptive methods. Data is obtained through observations, interviews, and documentation. Data analysis is done by reducing, presenting, and verifying data. The results of this study are mothers who work as domestic helpers in carrying out the role of early childhood independence in the family environment is done by taking the best time for the child, applying habits and discipline to the child, applying responsibility to the child, and providing rewards as motivation for children to continue to be encouraged to do independence.